Cooperativism and the solidarity economy: origin and history - Ramírez Díaz, Luis Francisco; Herrera Ospina, José de Jesús; Londoño Franco, Luis Fernando (Cooperativismo & Desarrollo, 2016)
Purpose: This article presents a systematic review of philosophical thought about the beginnings of the solidarity economy in the international and national context. Description: The development of the global economy requires new settings for thinking and the praxis of cooperativism or solidarity economies in the different activities that constitute the work of human beings, i.e., politics, society, economics, and culture, among others. This article describes the development of cooperativism and the solidarity economy from their conception to their contribution to the improvement of the quality of life of human beings, in addition toproviding a suitable setting for the approaches generated by the peace agreements in Colombia. Viewpoint: The article attempts to consider theoretical development from the different schools of thought that have arisen over time, from the concept of the solidarity economy as a response to the social crises that haveaccompanied civilization. Conclusions: Solidarity has historically been based on social development that seeks equity, justice, and sustainability for individuals. The description provided in this article allows us to establish the characterization of thinking about solidarity as a basis for the progress of modern communities.
Keywords: community; cooperativism; solidarity economy; humanity; society